Determination of Metal Hazard in the Processed E-Waste Types, Floor Dust and Pulverized Epoxy Powder Generated at an E-Waste Handling Site in India - P. Wagdevi; R. Jayakumar; P. Rajaguru; S. Muralidharan; Kaja Maideen, A.; Karthikeyan, Prakasham (Asian Journal of Engineering and Applied Technology, 2019)
At the e-waste handling site, the obsolete electronic items are dismantled and it releases dust laden with fine metallic fragments, called as floor dust. Further, the broken cables are denuded from its plastic insulation and shredded to fine grained pulverized epoxy powder. These two-processed e-wastes appear to contain metal residues. Hence, the aim is to examine the metal composition and identify the hazard, if any. Pulverized epoxy powder measured high values of Cd (7.43±0.48 μg/g), Pb (338.85±0.13 μg/g), Ni (534.62±53.68 μg/g), Li (30.12±0.02 μg/g), K (508109.90±31605.89 μg/g), Ca (817395.40±2.52 μg/g) and Na (3528.00±539.07 μg/g) while floor dust had high levels of Cr (39.61±5.78 μg/g), Cu (4778.14±861.91 μg/g), Zn (4172.88±821.75 μg/g), Fe (11164.90±1111.61 μg/g) and Se (1613.00±259.04 μg/g) with significant differences (p<0.05). The worn out electronic oddments attributes to high levels of metals. Principal component analysis could extract two components accounting for 78% variance in total. Although the values are less in comparison with the statutory limits, the processed e-wastes still pose a risk of metal toxicity due to their high volume. The composition of metals in the processed e-wastes presents us a new challenge to handle them.